1979
DOI: 10.1093/nar/6.1.321
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of low molecular weight RNA components A, C and D by polymerase II in α-amanitin-resistant hamster cells

Abstract: In an attempt to establish which RNA polymerase catalyzes the synthesis of the low molecular weight RNA components A, C and D, Ama 1 cells (mutant Chinese hamster cells) were used in experiments with addition of alpha-amanitin. Ama 1 cells contain an altered RNA polymerase II which is 800 times more resistant towards inhibition by alpha-amanitin than the wild type enzyme. Alpha-amanitin (up to 200 microgram/ml) added to these cells does not affect the synthesis of the low molecular weight RNAs A, C and D. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…An almost complete suppression of Ul RNA labeling was observed when in vitro transcription was carried out in the presence of a-amanitin at a concentration of 1 ,ug/ml (Fig. 2), consistent with previous evidence that Ul RNA is transcribed by RNA polymerase II (19,40). The most interesting result in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…An almost complete suppression of Ul RNA labeling was observed when in vitro transcription was carried out in the presence of a-amanitin at a concentration of 1 ,ug/ml (Fig. 2), consistent with previous evidence that Ul RNA is transcribed by RNA polymerase II (19,40). The most interesting result in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Human cells contain approximately 30 Ul RNA genes per haploid genome (27), clustered on chromosome 1 (26). Ul RNA is synthesized by RNA polymerase 11 (19,40) but, although the 5' sequences flanking several cloned human Ul genes are highly conserved (27,31), they lack the canonical promoter sequences characteristic of other polymerase II-transcribed genes (4). Moreover, the transcription unit of Ul RNA has not been clearly defined.…”
mentioning
confidence: 99%
“…The biosynthesis of snRNPs is itself complex, with several features different from mRNA transcription and processing. U1, U2, U4, and U5 RNAs are transcribed by polymerase II but, unlike most polymerase II transcripts (mRNA), are capped with trimethylguanosine (Ro-Choi et al 1976;Jensen et al 1979;Roop et al 1981;Kunkel and Pederson 1985). We and others have recently demonstrated that U6 RNA is transcribed by a different enzyme which, by the criteria of ~-amanitin sensitivity and competition for 5S gene transcription machinery, is likely to be RNA polymerase III (Kunkel et al 1986;Reddy et al 1987).…”
mentioning
confidence: 99%
“…Like other RNA polymerase II transcripts, such as mRNA, snRNAs are capped, and their synthesis is inhibited by a-amanitin (8). Unlike most polymerase II transcripts, snRNAs are metabolically stable, are not polyadenylated, and contain an unusual 2,2,7-trimethyl guanosine cap structure instead of the 7-methyl guanosine cap found on mRNA (for a review, see reference 31).…”
mentioning
confidence: 99%